A super abrasion alloy liner plate and a preparation method thereof
Patent Information
- Application Number
- CN202611449903.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-27
AI Technical Summary
以现有粉末冶金烧结、铸渗工艺为基础,通过非对称梯度多孔陶瓷预制体的结构设计、金属粘结剂的组分优化、预包覆造粒成型工艺与等温淬火热处理的协同匹配,解决现有陶瓷增强衬板整体韧性偏低的技术问题,实现耐磨性能、界面结合强度与冲击韧性的协同提升
采用非对称梯度结构实现性能精准匹配,耐磨与抗剥落协同提升。通过粒径、陶瓷占比、粘结剂含量的三重梯度设计,工作面实现高耐磨、背层实现强结合,与均匀结构预制体相比,本方案工作面耐磨性提升20%以上,有效解决了增强层易剥落的行业痛点。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wear-resistant steel technology, specifically relating to an ultra-wear-resistant alloy liner and its preparation method. Background Technology
[0002] In industries such as mining, cement, and power, the liners of ball mills and semi-autogenous mills are subjected to intense impact and cutting wear from abrasive materials such as ores for extended periods, making them one of the most frequently consumed and vulnerable parts. While traditional high-chromium cast iron liners possess a certain degree of wear resistance, they lack sufficient toughness under strong impact conditions, making them prone to fracture and premature failure.
[0003] Ceramic particle-reinforced metal matrix composites combine the high hardness and wear resistance of ceramics with the high toughness and impact resistance of metals, and are considered an important development direction to replace traditional single wear-resistant materials. Among them, ZTA ceramic particle-reinforced high-chromium cast iron matrix composites have become a research hotspot due to the high hardness and toughness of ZTA particles and their relatively close thermal expansion coefficient with that of the high-chromium cast iron matrix.
[0004] Current methods for preparing ZTA / high-chromium cast iron composites primarily employ powder metallurgy sintering to prepare porous ceramic preforms, followed by casting with molten high-chromium cast iron. However, existing technologies utilize an Fe-Ti binary system. Ti is a high-cost, reactive metal, and its high dosage significantly increases raw material costs. Furthermore, it offers limited improvement to interfacial bonding and still carries the risk of ceramic particle spalling under strong impact conditions, making it difficult to meet requirements for wear resistance and impact performance. Additionally, existing technologies simply mix ZTA particles with powdered metal binders before molding. Due to the significant density and particle size differences between the metal powder and ZTA ceramics, segregation easily occurs during mixing, resulting in extremely uneven binder distribution within the preform, severely impacting preform quality and interfacial consistency.
[0005] Therefore, there is an urgent need to develop a ZTA particle-reinforced high-chromium cast iron-based ultra-wear-resistant alloy liner with high interfacial bonding strength and balanced comprehensive performance to solve the above-mentioned technical problems. Summary of the Invention
[0006] This invention provides a ZTA particle-reinforced high-chromium cast iron-based ultra-wear-resistant alloy liner and its preparation method. Based on existing powder metallurgy sintering and casting infiltration processes, this invention addresses the technical problem of low overall toughness in existing ceramic-reinforced liners by synergistically matching the structural design of asymmetric gradient porous ceramic preforms, the composition optimization of the metal binder, and the pre-coating granulation molding process with isothermal quenching heat treatment. This achieves a synergistic improvement in wear resistance, interfacial bonding strength, and impact toughness. The working surface hardness reaches 68.5~69.1 HRC, and the impact energy is 9.2~10.1 J / cm². 2 With a relative wear rate of only 19-27%, it achieves a balanced match of high wear resistance, high toughness, and strong interface.
[0007] In a first aspect, the present invention relates to an ultra-wear-resistant alloy liner, comprising: a high-chromium cast iron matrix and an asymmetric porous ceramic preform made of ZTA ceramic particles embedded in the matrix; wherein: The ZTA ceramic particles comprise: ZTA particles with a particle size of 1.5-2.5 mm for the working surface layer, accounting for 50-58% of the total volume of the working surface layer mixture; and ZTA particles with a particle size of 2.5-3.5 mm for the back layer, accounting for 35-42% of the total volume of the back layer mixture. The metal binder comprises, by mass percentage: Ti 12-18%, Cr 3-6%, Al 0.5-1.5%, CeO2 0.3-0.8%, with the balance being Fe and unavoidable impurities; The asymmetric porous ceramic preform exhibits an asymmetric gradient distribution along its thickness: the amount of metal binder in the working layer is 6-9% of the mass of ZTA ceramic particles; the amount of metal binder in the back layer is 10-15% of the mass of ZTA ceramic particles; and there is a natural transition zone between the two layers formed by a gradual change in particle size. The chemical composition of the high-chromium cast iron matrix, by mass percentage, includes: C 2.8-3.4%, Cr 18-24%, Mo 1.5-2.5%, Ni 0.5-1.5%, Mn 0.8-1.2%, Si 0.4-0.8%, B 0.003-0.008%, RE 0.05-0.10%, S≤0.04%, P≤0.04%, with the balance being Fe and unavoidable impurities.
[0008] Preferably, the chemical composition of the ZTA ceramic particles by mass percentage includes: Al2O3 52-60%, ZrO2 36-45%, Y2O3 2-4%, and TiO2 ≤2%.
[0009] Preferably, the particle size of each element in the metal binder is: Fe powder ≤ 75 μm, Ti powder ≤ 45 μm, Cr powder ≤ 45 μm, Al powder ≤ 25 μm, and CeO2 powder ≤ 10 μm.
[0010] Preferably, the thickness of the asymmetric porous ceramic preform is 15-25 mm.
[0011] The working surface layer features a fine-grained design, a high ceramic content, and a low binder content. The fine particles have a large specific surface area, which can form a denser wear-resistant skeleton, effectively resisting the cutting and chiseling effects of abrasives; the high ceramic volume ratio maximizes the high hardness of ceramics and improves the wear resistance of the working surface; the low binder content reduces the proportion of metallic phase, preventing the preferential loss of metallic phase during wear and avoiding premature detachment of ceramic particles.
[0012] The backing layer features a coarse-grained design, low ceramic content, and high binder content. The coarse particles create larger pores, allowing for more thorough molten iron penetration and stronger mechanical interlocking. The low ceramic content reduces the thermal expansion difference between the ceramic phase and the metal matrix, alleviating interfacial thermal stress. The high binder content enhances the toughness and high-temperature strength of the backing layer preform, while the binder's good compatibility with the high-chromium cast iron matrix enables metallurgical fusion, fundamentally preventing the overall peeling off of the reinforcing layer.
[0013] At the layered loading interface, small particles of 1.5-2.5 mm and large particles of 2.5-3.5 mm are in contact with each other. In this invention, at the loading interface, the small particles in the working layer are partially embedded in the gaps between the large particles in the back layer, forming a transition zone with a continuous and gradual change in both particle size and ceramic volume fraction. This avoids the risk of stress concentration and interlayer cracking caused by abrupt changes in ceramic content in traditional multilayer precast structures.
[0014] The metal binder comprises, by mass percentage: Ti 12-18%, Cr 3-6%, Al 0.5-1.5%, CeO2 0.3-0.8%, with the balance being Fe and unavoidable impurities.
[0015] Ti: The core active element, diffuses to the surface of ZTA particles during high-temperature sintering, and reacts in situ with O elements in the ceramic lattice to form continuous and dense TiO. X The transition layer activates the ceramic surface, upgrading the mechanical bond between ceramic and metal to a metallurgical bond, significantly improving the interfacial bonding strength.
[0016] Cr: On the one hand, it dissolves in the Fe binder phase, improving the high-temperature strength and softening resistance of the binder and enhancing the preform's resistance to molten iron erosion; on the other hand, it can react with C in the matrix during casting to generate Cr-rich carbides, further strengthening the interfacial transition zone and reducing excessive dilution of the binder by the molten iron.
[0017] Al: A strong deoxidizing element that can remove oxygen and oxide inclusions from binder powder and purify the sintering interface; at the same time, a small amount of it is dissolved in the binder phase, which plays a role in solid solution strengthening and improves the bonding strength of the sintering neck.
[0018] CeO2: A rare earth oxide additive that can reduce interfacial energy and promote the wetting of ceramic particles by the binder phase during sintering; at the same time, it refines the structure of the binder phase, improves the toughness and thermal shock resistance of the binder, and reduces microcracks during the sintering and casting process of the preform.
[0019] Fe: The binder matrix phase, forming a continuous metallic skeleton to ensure the overall strength and toughness of the preform. Its composition is similar to that of high-chromium cast iron, allowing for complete metallurgical fusion during casting. Fe and Ti can form Fe2Ti intermetallic compounds, improving the high-temperature strength of the binder.
[0020] The chemical composition of the high-chromium cast iron matrix, by mass percentage, includes: C 2.8-3.4%, Cr 18-24%, Mo 1.5-2.5%, Ni 0.5-1.5%, Mn 0.8-1.2%, Si 0.4-0.8%, B 0.003-0.008%, RE 0.05-0.10%, S≤0.04%, P≤0.04%, with the balance being Fe and unavoidable impurities. Trace amounts of B can significantly reduce the surface tension of the molten iron, improving its wettability and penetration into the preform; simultaneously, B can improve hardenability and promote bainite transformation during isothermal quenching. RE can purify the molten iron, removing impurities such as O and S; during the casting process, RE preferentially accumulates at the molten iron / preform interface, further improving wettability and promoting metallurgical bonding.
[0021] Secondly, the present invention relates to a method for preparing the aforementioned ultra-wear-resistant alloy liner, comprising the following steps: S1: Preparation of Metal Binder Fe powder, Ti powder, Cr powder, Al powder, and CeO2 powder were weighed according to the specified ratio and mixed by high-energy ball milling under argon protection for 2-4 hours to obtain the metal binder. S2: Adhesive pre-coating granulation and layered filling molding (a) Adhesive pre-coating: The metal adhesive prepared in step S1 is mixed with a temporary adhesive solution to form a coating slurry; the pretreated ZTA ceramic particles are placed in a rotary granulator, and the coating slurry is sprayed in while the particles are rolling, so that the adhesive is uniformly coated on the surface of the ZTA particles. After drying at 80-120℃, coated particles are obtained; the temporary adhesive solution is a polyvinyl alcohol (PVA) aqueous solution with a concentration of 3-8 wt%. The working surface coating particles are prepared separately: 1.5-2.5mm ZTA particles are used, and the amount of metal binder is 6-9% of the mass of ZTA particles; the backing coating particles are prepared separately: 2.5-3.5mm ZTA particles are used, and the amount of metal binder is 10-15% of the mass of ZTA particles. (b) Layered loading: First, lay the back layer of coated particles in the mold and compact them with slight vibration; then lay the working layer of coated particles and compact them with slight vibration; due to the difference in particle size between the two ZTA layers and the loading order, a natural transition zone is formed at the interface. (c) Cold isostatic pressing: The mold after layered loading is subjected to cold isostatic pressing, with a pressure of 100-150MPa and a holding pressure of 30-60s; after demolding, an asymmetric preform blank is obtained. S3: Vacuum pressureless sintering The green blank obtained in step S2 is placed in a vacuum sintering furnace with a vacuum degree ≤10. -2 Pa, heated to 1260-1340℃, held for 2-3 hours; then furnace cooled to room temperature to obtain an asymmetric porous ceramic preform; S4: Casting-infiltration composite The preform obtained in step S3 is placed in a mold preheated to 200-300℃, with the working side of the preform facing the mold cavity; a high-chromium cast iron matrix alloy is smelted at a furnace temperature of 1450-1480℃ and a pouring temperature of 1420-1460℃. Bottom pouring is used to allow the molten iron to penetrate into the pores of the preform under gravity and capillary action. After solidification, a composite liner billet is obtained. S5: Composite Heat Treatment The composite liner blank is preheated at 600-650℃ for 1-2 hours, then slowly heated to 950-980℃ and held for 2-3 hours for solution treatment; then it is quickly transferred to a nitrate bath at 280-320℃ and held isothermally for 5-6 hours to obtain a lower bainitic matrix structure; after isothermal quenching, it is air-cooled to room temperature, and then tempered at 220-260℃ for 3-4 hours to obtain the super wear-resistant alloy liner.
[0022] Preferably, in step S2(a), the amount of the temporary adhesive solution used is 10-20% of the mass of the metal adhesive powder.
[0023] Preferably, the frequency of the slight vibration compaction in step S2(b) is 10-20Hz, the amplitude is 0.5-1mm, and the vibration time for each layer is 1-2min.
[0024] A pre-coating granulation process is employed. Traditional direct mixing processes easily lead to binder powder agglomeration and insufficient filling of gaps between large particles, resulting in uneven porosity and local lack of sintering necks in the preform. This invention employs a rotary granulation pre-coating process, mixing metal binder powder with a temporary binder solution to prepare a coating slurry. The temporary binder solution is a polyvinyl alcohol (PVA) aqueous solution with a concentration of 3-8 wt%, and the amount used is 10-20% of the mass of the metal binder powder. As a temporary binder, PVA can completely decompose and volatilize in the early stage of sintering (200-400℃), leaving no residue and not contaminating the interface. The pretreated ZTA ceramic particles are placed in a rotary granulation device. While the ZTA particles are continuously rolling, the coating slurry is uniformly sprayed in through an atomizing nozzle. The metal powder in the slurry adheres uniformly to the surface of the ZTA particles under the adhesion of PVA, and with rolling and compaction, core-shell structured coated particles are formed. This ensures that the binder powder is evenly coated on the surface of each ZTA particle, guaranteeing that a uniform sintering neck can be formed at each particle contact point during sintering, significantly improving the porosity and strength consistency of the preform; at the same time, it avoids the binder powder from accumulating and blocking the channels in the pores, ensuring a smooth flow path for the molten iron during casting.
[0025] To address the issue of increased brittleness in ceramic-reinforced materials, this invention employs an isothermal quenching process to obtain a lower bainitic matrix. Lower bainitic matrix combines high hardness with excellent toughness, effectively buffering stress concentration between ceramic particles and reducing crack initiation and propagation. Combined with low-temperature tempering to relieve stress, the microstructure and properties are further stabilized. Simultaneously, a preheating and slow-heating heating regime is used to avoid interfacial thermal stress cracking caused by the difference in thermal expansion between ceramic and metal, ensuring the integrity of the composite structure.
[0026] The beneficial effects of this invention are as follows: An asymmetric gradient structure is adopted to achieve precise performance matching, synergistically improving wear resistance and anti-stripping properties. Through a triple gradient design of particle size, ceramic ratio, and binder content, the working surface achieves high wear resistance and the backing layer achieves strong bonding. Compared with uniform structure precast bodies, this solution improves the wear resistance of the working surface by more than 20%, effectively solving the industry pain point of easy peeling of the reinforcing layer.
[0027] The five-element active binder strengthens the interfacial metallurgical bond, resulting in excellent high-temperature performance of the preform. The synergistic effect of the Fe-Ti-Cr-Al-CeO2 five-element system, through TiO2... x The transition layer achieves ceramic-metal metallurgical bonding, and enhances the high-temperature strength and toughness of the binder through Cr, Al, and CeO2.
[0028] The pre-coating process achieves uniform coating of the binder. Combined with layered loading and cold isostatic pressing, there is no binder agglomeration or local material shortage defects. With bottom-pouring stable casting, the casting and infiltration qualification rate reaches over 99%. It has good stability in mass production and is suitable for large-scale industrial production.
[0029] Isothermal quenching optimizes the matrix structure, resulting in a superior balance between hardness and toughness. The lower bainitic matrix structure maintains high hardness to support ceramic particles while also possessing excellent toughness to buffer stress. The working surface of the liner plate achieves a hardness of 68.5~69.1 HRC and an impact energy of 9.2~10.1 J / cm². 2 With a relative wear rate of only 19-27%, it achieves a balanced match of high wear resistance, high toughness, and strong interface, making it suitable for a wider range of applications. Detailed Implementation
[0030] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] The components and preparation process of the embodiments are as follows: A super wear-resistant alloy liner includes: a high-chromium cast iron matrix and an asymmetric porous ceramic preform made of ZTA ceramic particles embedded in the matrix; wherein: The ZTA ceramic particles comprise: ZTA particles with a particle size of 1.5-2.5 mm for the working surface layer, accounting for 50-58% of the total volume of the working surface layer mixture; and ZTA particles with a particle size of 2.5-3.5 mm for the back layer, accounting for 35-42% of the total volume of the back layer mixture. The metal binder comprises, by mass percentage: Ti 12-18%, Cr 3-6%, Al 0.5-1.5%, CeO2 0.3-0.8%, with the balance being Fe and unavoidable impurities; The asymmetric porous ceramic preform exhibits an asymmetric gradient distribution along its thickness: the amount of metal binder in the working layer is 6-9% of the mass of ZTA ceramic particles; the amount of metal binder in the back layer is 10-15% of the mass of ZTA ceramic particles; and there is a natural transition zone between the two layers formed by a gradual change in particle size. The chemical composition of the high-chromium cast iron matrix, by mass percentage, includes: C 2.8-3.4%, Cr 18-24%, Mo 1.5-2.5%, Ni 0.5-1.5%, Mn 0.8-1.2%, Si 0.4-0.8%, B 0.003-0.008%, RE 0.05-0.10%, S≤0.04%, P≤0.04%, with the balance being Fe and unavoidable impurities.
[0032] The chemical composition of the ZTA ceramic particles, by mass percentage, includes: Al₂O₃ 52-60%, ZrO₂ 36-45%, Y₂O₃ 2-4%, and TiO₂ ≤2%. The particle sizes of the raw materials in the metal binder are: Fe powder ≤75μm, Ti powder ≤45μm, Cr powder ≤45μm, Al powder ≤25μm, and CeO₂ powder ≤10μm.
[0033] The thickness of the asymmetric porous ceramic preform is 15-25 mm.
[0034] The method for preparing the aforementioned ultra-wear-resistant alloy liner is characterized by comprising the following steps: S1: Preparation of Metal Binder Fe powder, Ti powder, Cr powder, Al powder, and CeO2 powder were weighed according to the specified ratio and mixed by high-energy ball milling under argon protection for 2-4 hours to obtain the metal binder. S2: Adhesive pre-coating granulation and layered filling molding (a) Adhesive pre-coating: The metal adhesive prepared in step S1 is mixed with a temporary adhesive solution to form a coating slurry; the pretreated ZTA ceramic particles are placed in a rotary granulator, and the coating slurry is sprayed in while the particles are rolling, so that the adhesive is uniformly coated on the surface of the ZTA particles. After drying at 80-120℃, coated particles are obtained; the temporary adhesive solution is a polyvinyl alcohol (PVA) aqueous solution with a concentration of 3-8 wt%. The working surface coating particles are prepared separately: 1.5-2.5mm ZTA particles are used, and the amount of metal binder is 6-9% of the mass of ZTA particles; the backing coating particles are prepared separately: 2.5-3.5mm ZTA particles are used, and the amount of metal binder is 10-15% of the mass of ZTA particles. (b) Layered loading: First, lay the back layer of coated particles in the mold and compact them with slight vibration; then lay the working layer of coated particles and compact them with slight vibration; due to the difference in particle size between the two ZTA layers and the loading order, a natural transition zone is formed at the interface. (c) Cold isostatic pressing: The mold after layered loading is subjected to cold isostatic pressing, with a pressure of 100-150MPa and a holding pressure of 30-60s; after demolding, an asymmetric preform blank is obtained. S3: Vacuum pressureless sintering The green blank obtained in step S2 is placed in a vacuum sintering furnace with a vacuum degree ≤10. -2 Pa, heated to 1260-1340℃, held for 2-3 hours; then furnace cooled to room temperature to obtain an asymmetric porous ceramic preform; S4: Casting-infiltration composite The preform obtained in step S3 is placed in a mold preheated to 200-300℃, with the working side of the preform facing the mold cavity; a high-chromium cast iron matrix alloy is smelted at a furnace temperature of 1450-1480℃ and a pouring temperature of 1420-1460℃. Bottom pouring is used to allow the molten iron to penetrate into the pores of the preform under gravity and capillary action. After solidification, a composite liner billet is obtained. S5: Composite Heat Treatment The composite liner blank is preheated at 600-650℃ for 1-2 hours, then slowly heated to 950-980℃ and held for 2-3 hours for solution treatment; then it is quickly transferred to a nitrate bath at 280-320℃ and held isothermally for 5-6 hours to obtain a lower bainitic matrix structure; after isothermal quenching, it is air-cooled to room temperature, and then tempered at 220-260℃ for 3-4 hours to obtain the super wear-resistant alloy liner.
[0035] In step S2(a), the amount of the temporary adhesive solution used is 10-20% of the mass of the metal adhesive powder.
[0036] In step S2(b), the frequency of the slight vibration compaction is 10-20Hz, the amplitude is 0.5-1mm, and the vibration time for each layer is 1-2min.
[0037] The total thickness of the prefabricated body in each embodiment and comparative example is 20 mm, of which the working surface layer is 8 mm thick and the back layer is 12 mm thick.
[0038] Example 1: Component Parameters Working surface layer: ZTA particle size 1.5~2.5mm, ceramic volume ratio 55%, metal binder dosage 7.5% of ZTA mass; Backing layer: ZTA particle size 2.5~3.5mm, ceramic volume ratio 38%, metal binder amount 12% of ZTA mass; Metal binder composition (mass percentage): Ti 15%, Cr 4.5%, Al 1.0%, CeO 20.5%, balance Fe; High-chromium cast iron matrix composition (mass percentage): C 3.1%, Cr 21%, Mo 2.0%, Ni 1.0%, Mn 1.0%, Si 0.6%, B 0.005%, RE 0.08%, S 0.025%, P 0.03%, balance Fe.
[0039] Preparation process S1: Weigh the metal powder according to the ratio, and ball mill it for 3 hours under argon protection to obtain binder powder; S2: Prepare a 5wt% PVA aqueous solution, the amount of which is 15% of the binder mass, to make a coating slurry; rotate and granulate two types of ZTA particles to coat them, and dry them at 100℃; load the material in layers, vibrate at 15Hz and 0.8mm amplitude for 1.5min to compact it; hold it under cold isostatic pressing at 120MPa for 45s to obtain a green blank; S3: Vacuum sintering, vacuum degree 5×10 -3 Pa, heated to 1280℃, held for 2.5h, and cooled to room temperature in the furnace to obtain a porous ceramic preform; S4: The preform is preheated to 250℃ and then fixed in the mold. The high-chromium cast iron is taken out of the furnace at 1465℃ and poured at 1440℃ using the bottom pouring method. S5: Preheat at 620℃ for 1.5h, slowly increase to 965℃ and hold for 2.5h; transfer to a 300℃ nitrate bath for isothermal treatment for 5h; air cool and then temper at 240℃ for 3.5h, then cool with the furnace.
[0040] Example 2: Component Parameters Working surface layer: ZTA particle size 1.5~2.5mm, ceramic volume ratio 50%, metal binder dosage is 8% of ZTA particle mass; Backing layer: ZTA particle size 2.5~3.5mm, ceramic volume ratio 35%, metal binder amount 13% of ZTA particle mass; Metal binder composition (mass percentage): Ti 12%, Cr 4%, Al 1.5%, CeO 20.5%, balance Fe; High-chromium cast iron matrix composition (mass percentage): C 3.0%, Cr 18%, Mo 2.0%, Ni 0.8%, Mn 1.0%, Si 0.5%, B 0.003%, RE 0.07%, S 0.03%, P 0.032%, balance Fe.
[0041] Preparation process S1: Weigh each metal powder according to the ratio, and ball mill them for 2 hours under argon protection to obtain uniform binder powder. S2: Prepare a 5wt% PVA aqueous solution, the amount of which is 20% of the mass of the binder powder, to make a coating slurry; rotate and granulate two types of ZTA particles to coat them, and dry them at 100℃; after layering and loading, apply vibration at 10Hz and amplitude of 0.8mm for 2min to compact; use cold isostatic pressing at 150MPa for 30s to demold and obtain the preformed voxel blank; S3: Place the green blank in a vacuum sintering furnace with a vacuum degree of 6×10⁻⁶. -3 Pa, heated to 1260℃, held for 2.5h, and cooled to room temperature in the furnace to obtain a porous ceramic preform; S4: After preheating the preform to 250℃, fix it in the mold; high-chromium cast iron is taken out of the furnace at 1460℃, and the pouring temperature is controlled at 1430℃, using bottom pouring for stable pouring. S5: Preheat at 640℃ for 1.3h, then slowly heat to 960℃ and hold for 2h; then quickly transfer to a 290℃ nitrate bath and hold at an isothermal temperature for 5.5h; after air cooling to room temperature, temper at 230℃ for 3.5h, and then cool with the furnace.
[0042] Example 3: Component Parameters Working surface layer: ZTA particle size 1.5~2.5mm, ceramic volume ratio 58%, metal binder amount 7% of ZTA particle mass; Backing layer: ZTA particle size 2.5~3.5mm, ceramic volume ratio 42%, metal binder amount 11% of ZTA particle mass; Metal binder composition (mass percentage): Ti 16%, Cr 6%, Al 0.8%, CeO 20.3%, balance Fe; High-chromium cast iron matrix composition (mass percentage): C 3.3%, Cr 22%, Mo 1.8%, Ni 1.5%, Mn 0.9%, Si 0.8%, B 0.006%, RE 0.05%, S 0.028%, P 0.03%, balance Fe.
[0043] Preparation process S1: Weigh each metal powder according to the ratio, and ball mill them under argon protection for 3.5 hours to obtain a uniform binder powder; S2: Prepare an 8wt% PVA aqueous solution, the amount of which is 12% of the binder powder mass, to make a coating slurry; rotate and granulate two types of ZTA particles of different sizes for coating, and dry at 120℃; after layering and loading, apply vibration at 18Hz and amplitude of 0.5mm for 1min to compact; use cold isostatic pressing at 110MPa for 50s to demold and obtain the preformed voxel blank; S3: Place the green blank in a vacuum sintering furnace with a vacuum degree of 4×10⁻⁶. -3 Pa, heated to 1300℃, held for 3 hours, and cooled to room temperature in the furnace to obtain a porous ceramic preform; S4: After preheating the preform to 200℃, fix it in the mold; high-chromium cast iron is taken out of the furnace at 1470℃, and the pouring temperature is controlled at 1420℃, using bottom pouring for stable pouring; S5: Preheat at 600℃ for 2 hours, then slowly heat to 980℃ and hold for 2.5 hours; then quickly transfer to a 300℃ nitrate bath and hold at an isothermal temperature for 6 hours; after air cooling to room temperature, temper at 260℃ for 3 hours, and then cool with the furnace to obtain the finished lining plate.
[0044] Example 4: Component Parameters Working surface layer: ZTA particle size 1.5~2.5mm, ceramic volume ratio 53%, metal binder dosage is 9% of ZTA particle mass; Backing layer: ZTA particle size 2.5~3.5mm, ceramic volume ratio 39%, metal binder amount 10% of ZTA particle mass; Metal binder composition (mass percentage): Ti 14%, Cr 5%, Al 0.5%, CeO 20.8%, balance Fe; High-chromium cast iron matrix composition (mass percentage): C 2.8%, Cr 24%, Mo 2.5%, Ni 1.0%, Mn 1.2%, Si 0.4%, B 0.008%, RE 0.10%, S 0.02%, P 0.025%, balance Fe.
[0045] Preparation process S1: Weigh each metal powder according to the ratio, and ball mill them for 4 hours under argon protection to obtain uniform binder powder. S2: Prepare a 3wt% PVA aqueous solution, the amount of which is 15% of the mass of the binder powder, to make a coating slurry; rotate and granulate two types of ZTA particles to coat them, and dry them at 90℃; after layering and loading, apply vibration at 20Hz and amplitude of 1mm to compact for 1.5min; use cold isostatic pressing at 130MPa for 60s, and demold to obtain the preformed voxel blank; S3: Place the green blank in a vacuum sintering furnace with a vacuum degree of 5×10⁻⁶. -3 Pa, heated to 1330℃, held for 2 hours, and cooled to room temperature in the furnace to obtain a porous ceramic preform; S4: Preheat the preform to 300℃ and fix it in the mold; high chromium cast iron is taken out of the furnace at 1480℃, and the pouring temperature is controlled at 1460℃, using bottom pouring for stable pouring. S5: Preheat at 650℃ for 1 hour, then slowly heat to 950℃ and hold for 3 hours; then quickly transfer to a 320℃ nitrate bath and hold at an isothermal temperature for 6 hours; after air cooling to room temperature, temper at 220℃ for 4 hours, and then cool with the furnace to obtain the finished lining plate.
[0046] The following comparative example is Example 1. Comparative Example 1: Uniform precast structure The preform is made of 1.5~2.5mm ZTA particles, with ceramic accounting for 55% of the volume and binder accounting for 7.5%, which are evenly distributed; the remaining components and processes are the same as in Example 1.
[0047] Comparative Example 2: The binder contains 10% Ti element, and the remaining components and processes are the same as in Example 1.
[0048] Comparative Example 3: The binder does not contain CeO2, and the corresponding proportion is supplemented by Fe; the remaining components and processes are the same as in Example 1.
[0049] Comparative Example 4: The ceramic volume ratio of the working surface layer is 47% (lower than the lower limit of 50% in the claims), and the amount of adhesive remains unchanged; the remaining components and processes are the same as in Example 1.
[0050] Comparative Example 5: The amount of adhesive used in the working surface layer is 11% of the ZTA mass (higher than the upper limit of 9% in claim 1); the remaining components and processes are the same as in Example 1.
[0051] Comparative Example 6: The amount of backing adhesive was 8% of the ZTA mass (lower than the 10% lower limit of claim); the remaining components and processes were the same as in Example 1.
[0052] Comparative Example 7: The ZTA particles in the working surface layer have a particle size of 1.0-1.5 mm, and the ceramic volume ratio and binder dosage remain unchanged; the other components and processes are the same as in Example 1.
[0053] Comparative Example 8: The pre-coating granulation process was eliminated, and ZTA particles were directly mechanically mixed with binder powder and then loaded into the mold.
[0054] The remaining components and processes are the same as in Example 1.
[0055] The following performance tests were performed on the embodiments and comparative examples: Working surface hardness: The HRC hardness of the working surface of the liner was tested using a Rockwell hardness tester in accordance with GB / T230.1 Rockwell hardness test method for metallic materials.
[0056] Impact toughness: According to GB / T229 Charpy pendulum impact test method for metallic materials, U-notch specimens containing complete ceramic reinforcement layer and matrix were prepared, and the impact energy was tested on a pendulum impact testing machine.
[0057] Relative wear rate: Wear tests were conducted using an MLD-10 dynamic load abrasive wear tester. The wear amount of ordinary high-chromium cast iron under the same test conditions was used as the benchmark (recorded as 100%). The relative wear rate of the sample was calculated. The lower the value, the better the wear resistance.
[0058] Table 1 Performance data of the examples and comparative examples
[0059] As can be seen from Table 1, the overall performance of Examples 1-4 of the present invention is significantly better than that of the comparative examples, with a working surface hardness of 68.5-69.1 HRC and an impact energy of 9.2-10.1 J / cm. 2 With a relative wear rate of only 19-27%, it achieves a balanced match of high wear resistance, high toughness, and strong interface.
[0060] Comparative Example 1 verifies the role of asymmetric gradient structures: the toughness of uniform structures decreases significantly, and the overall performance of the prefabricated body is uneven, proving that gradient design can accurately match service requirements and maximize performance.
[0061] Comparative Example 2 verifies the core role of Ti: TiO cannot be formed if the Ti content is outside the scope of this application. x The metallurgical transition layer, the interface bonding step, and the decrease in the infiltration qualification rate prove that Ti is the key component for achieving interface metallurgical bonding.
[0062] Comparative Example 3 verified the role of rare earth oxides: the lack of CeO2 reduced the wettability of the binder, and also reduced the impact toughness and wear resistance.
[0063] Comparative Example 4 verified the correlation between ceramic proportion and wear resistance: insufficient ceramic proportion leads to weakening of the wear-resistant skeleton and a significant decrease in wear resistance.
[0064] Comparative Examples 5-6 verified the special effect of the adhesive content in the working surface and backing layer, which, when outside the scope of this application, affects the bonding strength and overall performance of the steel.
[0065] Comparative Example 7 verified the special selection of ZTA particle size. If the particle size is too small, it will be difficult to uniformly infiltrate the material, thus affecting the performance.
[0066] Comparative Example 8 verified the role of the pre-coating process: direct mixing leads to uneven distribution of binder, which in turn affects performance. Pre-coating granulation is an effective means to improve the uniformity of the structure.
[0067] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
Claims
1. A super wear-resistant alloy liner, characterized in that, include: A high-chromium cast iron matrix and an asymmetric porous ceramic preform made of ZTA ceramic particles embedded in the matrix; wherein: The ZTA ceramic particles comprise: ZTA particles with a particle size of 1.5-2.5 mm for the working surface layer, accounting for 50-58% of the total volume of the working surface layer mixture; and ZTA particles with a particle size of 2.5-3.5 mm for the back layer, accounting for 35-42% of the total volume of the back layer mixture. The metal binder comprises, by mass percentage: Ti 12-18%, Cr 3-6%, Al 0.5-1.5%, CeO2 0.3-0.8%, with the balance being Fe and unavoidable impurities; The asymmetric porous ceramic preform exhibits an asymmetric gradient distribution along its thickness: the amount of metal binder in the working layer is 6-9% of the mass of ZTA ceramic particles; the amount of metal binder in the back layer is 10-15% of the mass of ZTA ceramic particles; and there is a natural transition zone between the two layers formed by a gradual change in particle size. The chemical composition of the high-chromium cast iron matrix, by mass percentage, includes: C 2.8-3.4%, Cr 18-24%, Mo 1.5-2.5%, Ni 0.5-1.5%, Mn 0.8-1.2%, Si 0.4-0.8%, B 0.003-0.008%, RE 0.05-0.10%, S≤0.04%, P≤0.04%, with the balance being Fe and unavoidable impurities.
2. The ultra-wear-resistant alloy liner according to claim 1, characterized in that, The chemical composition of the ZTA ceramic particles by mass percentage includes: Al2O3 52-60%, ZrO2 36-45%, Y2O3 2-4%, TiO2 ≤2%.
3. The ultra-wear-resistant alloy liner according to claim 1, characterized in that, The particle size of each element in the metal binder is as follows: Fe powder ≤ 75 μm, Ti powder ≤ 45 μm, Cr powder ≤ 45 μm, Al powder ≤ 25 μm, CeO2 powder ≤ 10 μm.
4. The ultra-wear-resistant alloy liner according to claim 1, characterized in that, The thickness of the asymmetric porous ceramic preform is 15-25 mm.
5. A method for preparing an ultra-wear-resistant alloy liner as described in any one of claims 1-4, characterized in that, Includes the following steps: S1: Preparation of Metal Binder Fe powder, Ti powder, Cr powder, Al powder, and CeO2 powder were weighed according to the specified ratio and mixed by high-energy ball milling under argon protection for 2-4 hours to obtain the metal binder. S2: Adhesive pre-coating granulation and layered filling molding (a) Adhesive pre-coating: The metal adhesive prepared in step S1 is mixed with a temporary adhesive solution to form a coating slurry; the pretreated ZTA ceramic particles are placed in a rotary granulator, and the coating slurry is sprayed in while the particles are rolling, so that the adhesive is uniformly coated on the surface of the ZTA particles. After drying at 80-120℃, coated particles are obtained; the temporary adhesive solution is a polyvinyl alcohol (PVA) aqueous solution with a concentration of 3-8 wt%. The working surface coating particles are prepared separately: 1.5-2.5mm ZTA particles are used, and the amount of metal binder is 6-9% of the mass of ZTA particles; the backing coating particles are prepared separately: 2.5-3.5mm ZTA particles are used, and the amount of metal binder is 10-15% of the mass of ZTA particles. (b) Layered loading: First, lay the back layer of coated particles in the mold and compact them with slight vibration; then lay the working layer of coated particles and compact them with slight vibration; due to the difference in particle size between the two ZTA layers and the loading order, a natural transition zone is formed at the interface. (c) Cold isostatic pressing: The mold after layered loading is subjected to cold isostatic pressing, with a pressure of 100-150MPa and a holding pressure of 30-60s; after demolding, an asymmetric preform blank is obtained. S3: Vacuum pressureless sintering The green body obtained in step S2 is placed in a vacuum sintering furnace with a vacuum degree ≤10-2Pa, heated to 1260-1340℃, and held for 2-3 hours; then the furnace is cooled to room temperature to obtain an asymmetric porous ceramic preform. S4: Casting-infiltration composite The preform obtained in step S3 is placed in a mold preheated to 200-300℃, with the working side of the preform facing the mold cavity; a high-chromium cast iron matrix alloy is melted at a furnace temperature of 1450-1480℃ and a pouring temperature of 1420-1460℃. Bottom pouring is used to allow the molten iron to penetrate into the pores of the preform under gravity and capillary action. After solidification, a composite liner billet is obtained. S5: Composite Heat Treatment The composite liner blank is preheated at 600-650℃ for 1-2 hours, then slowly heated to 950-980℃ and held for 2-3 hours for solution treatment; then it is quickly transferred to a nitrate bath at 280-320℃ and held isothermally for 5-6 hours to obtain a lower bainitic matrix structure; after isothermal quenching, it is air-cooled to room temperature, and then tempered at 220-260℃ for 3-4 hours to obtain the super wear-resistant alloy liner.
6. The preparation method according to claim 5, characterized in that, In step S2(a), the amount of the temporary adhesive solution used is 10-20% of the mass of the metal adhesive powder.
7. The preparation method according to claim 5, characterized in that, In step S2(b), the frequency of the slight vibration compaction is 10-20Hz, the amplitude is 0.5-1mm, and the vibration time for each layer is 1-2min.
